Competitive ability of parasitized Drosophila larvae - Tien, N; Boyle, D; Kraaijeveld, A; Godfray, C (2001)
Knowledge of the cost of parasitism and the competitive ability of parasitized larvae is important for understanding the evolution of resistance. We used larvae of two Drosophila species as hosts for two parasitoid species which differ in their counter-resistance mechanism. Parasitism by Leptopilina heterotoma leads to a reduction in survival, in contrast to parasitism by Asobara tabida. This can be explained by L. heterotoma having a counter-defence mechanism that actively interferes with the host's immune system. Parasitized D. melanogaster larvae, which can encapsulate the parasitoid's egg to some degree, tend to suffer from a slight reduction in competitive ability, as opposed to parasitized D. subobscura larvae, which are unable to mount an immune response to parasitoids. Combined with earlier work, our results suggest that, in this system, the costs of actual defence are lower than the costs of maintaining an efficient immune system.